Who belongs to the swiss body politique—A diaspora perspective - King-Savic, Sandra (Frontiers in Political Science, 2023)
In this paper, I try to better understand the intersection between ‘integration’ in legal terms, and how long term resident ‘non-citizens’ and migrants from the former Socialist Federal Republic of Yugoslavia (SFRY) situate themselves in narratives of belonging vis a vis the normative power structure that constitutes the Swiss body politique. More specifically, how do labor- and forced migrants from former Yugoslavia negotiate the shifting understanding of ‘integration’ in Switzerland in legal and social terms? Former-Yugoslavs constitute not only a comparatively large number of ‘non-citizens’ in Switzerland. Individuals from-and-with-connections to this community also embody numerous labels and categories of migrant that statistical databases, the media, and legal practices attach to them since the 1970s. Key-findings in this paper illustrate a two-tiered narrative: ‘non-citizens’ maintain(ed) their pursuit of not attracting attention to their persona – a strategy that lets individuals disappear within the larger society. Ensuing Europeanization processes, coupled with the Wars of Yugoslav Succession during the 1990s present a dual rupture that brings to the fore othering processes, and a seemingly tightening sociolegal basis of belonging to the Swiss body politique. Hitherto examined data suggests that interlocutors pursue a ‘positive essentialist frame’ to counter exclusionary narratives ‘non-citizens’ experience so as to postulate ‘rights claims’. Interviewees, in other words, are active in diaspora-connections and networks to support and aid each-other when legal and socio-political questions arise, but also to actively influence the political and legal landscape in Switzerland.